THE ROLE OF HUMAN CAPITAL IN IMPROVING ENTERPRISE EFFICIENCY: MODERN APPROACHES - Ochilov, Akram Odilovich; Khasanova, Aziza Ikromovna (THE INNOVATION ECONOMY, 2026)
This article examines the role of human capital in enhancing enterprise efficiency. Human capital, consisting of employees’ knowledge, skills, and experience, is a crucial factor in increasing competitiveness and ensuring economic effectiveness. The study explores modern approaches to human capital development, including employee training and development, improving motivation systems, and implementing innovative technologies to enhance enterprise performance.